A thermodynamics-based multi-physics constitutive model for variably saturated fractured sorptive rocks. (October 2022) - Siddiqui, Mohammed Abdul Qadeer; Serati, Mehdi; Regenauer-Lieb, Klaus; Roshan, Hamid
Abstract: A multi-physics constitutive mathematical model is developed using non-equilibrium thermodynamics and continuum mechanics to investigate the temporal changes in the poromechanical behaviour of variably saturated sorptive shale rocks during gas production. The model specifically integrates the effects of matrix gas desorption and fracture two-fluid flow on bulk behaviour. The working of the model is studied through the numerical example of gas production from a continuum quarter wellbore geometry solved by the finite element method. The numerical results support the field observations that gas productivity remains unaffected during early production operations whereas the water recovery is strongly dependent on capillary pressure redistribution in the fracture network induced by the applied drawdown. Although the drawdown is limited by field operations, a higher drawdown will not necessarily result in more water production unless the capillary forces are altered in the water-wet micro-fracture network. The sensitivity analysis showed important parameters which if not incorporated into the constitutive model fail to accurately capture the bulk behaviour such as the presence of water in the fracture network, fracture permeability, and fractal dimension (representing the pore structure). It was shown how neglecting two-fluid flow and multi-physics effects in the fracture network can have significant impacts on the accuracy of gas production data. The research findings provide valuable insights to understand how poromechanics coupled with capillarity and desorption plays a role in causing bulk volumetric changes during gas production from shale formations.